Canaliser ou décupler l’agressivité des élèves en EPS ? L’exemple de la boxe française - Teddy Mayeko; Jérôme Frigout; Olivier Degrenne; Benjamin Le Gall (Éducation et Socialisation)
The study of aggressiveness in combat sports has already been the subject of much debate in the international research literature. Most often, the aggressive behaviours of practitioners are apprehended from questionnaires allowing to infer their personality traits and their dispositions to act. This research, carried out in physical and sports education (PSE), proposes to measure the level of aggressiveness of students practising French boxing by using a direct observation method in free assault (n = 91 ; boxers = 182 ; females = 79 ; males = 103). The quantitative method chosen (p